The relation among vague filters and Residuated Lattices - Illakiya, R.; Sanawaz, S.Muhamead; Selvi, Senthamil; Kavitha,; Rajalakshmi,; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
The focus of this paper is to develop The relation between the vague filters and residuated lattices, and its essential properties are investigated. Characterizations of vague filters in residuated lattice are established. We discuss some properties of vague filters in terms of its level subsets. Also the notion of Extended pair of vague filter is introduced and characterize their properties.